2009
DOI: 10.1364/ao.48.003654
|View full text |Cite
|
Sign up to set email alerts
|

Translational-symmetry alternating phase shifting mask grating mark used in a linear measurement model of lithographic projection lens aberrations

Abstract: A linear measurement model of lithographic projection lens aberrations is studied numerically based on the Hopkins theory of partially-coherent imaging and positive resist optical lithography (PROLITH) simulation. In this linearity model, the correlation between the mark's structure and its sensitivities to aberrations is analyzed. A method to design a mark with high sensitivity is proved and declared. By use of this method, a translational-symmetry alternating phase shifting mask (Alt-PSM) grating mark is red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The ultra-small RSS indicates that the linearity between BFS and retardance is excellent and the definition of the sensitivity is adoptable. The astigmatism and spherical aberrations are adjustable in advanced lithographic tools 13 , and the linear relationship between BFS and scalar even aberrations are verified by Qiu et al 14 . Therefore, a polarization aberration compensation method can be proposed by adjusting the scalar even aberrations to minimize the BFS caused by radially symmetric retardances.…”
Section: Linear Relationship Between Bfs and Aberrationmentioning
confidence: 86%
“…The ultra-small RSS indicates that the linearity between BFS and retardance is excellent and the definition of the sensitivity is adoptable. The astigmatism and spherical aberrations are adjustable in advanced lithographic tools 13 , and the linear relationship between BFS and scalar even aberrations are verified by Qiu et al 14 . Therefore, a polarization aberration compensation method can be proposed by adjusting the scalar even aberrations to minimize the BFS caused by radially symmetric retardances.…”
Section: Linear Relationship Between Bfs and Aberrationmentioning
confidence: 86%
“…The variation range of the partial coherence is 0.3-0.8. The accuracy of the aberration measurement can be estimated by [16,17] …”
Section: B Measurement Performance Evaluationmentioning
confidence: 99%
“…The Zernike coefficients are calculated directly from the image displacements of the mark at multiple NA and partial coherence factor σ settings through a matrix of sensitivities, which is a function of the corresponding multiple NA/σ settings. Wang et al recently reported a series of TAMIS based techniques to improve the measurement accuracy of coma and even aberrations by optimization of the test marks using phase-shifting gratings [9][10][11][12]. Although the main advantage of TAMIS and its improved techniques is to present a simplified linear model in a simple form that can be fully characterized by a matrix of sensitivities, there is no compact analytical formulation for the matrix of sensitivities itself.…”
Section: Introductionmentioning
confidence: 99%